Clinical characteristics and prognosis of patients admitted for heart failure: A 5-year retrospective study of African patients. (1st July 2017) - Bonsu, Kwadwo Osei; Owusu, Isaac Kofi; Buabeng, Kwame Ohene; Reidpath, Daniel D.; Kadirvelu, Amudha
Abstract: Background: Mortality associated with heart failure (HF) remains high. There are limited clinical data on mortality among HF patients from African populations. We examined the clinical characteristics, long-term outcomes, and prognostic factors of African HF patients with preserved, mid-range or reduced left ventricular ejection fraction (LVEF). Methods and results: We conducted a retrospective longitudinal cohort study of individuals aged ≥ 18 years discharged from first HF admission between January 1, 2009 and December 31, 2013 from the Cardiac Clinic, Directorate of Medicine of the Komfo Anokye Teaching Hospital, Ghana. A total of 1488 patients diagnosed of HF were included in the analysis. Of these, 345 patients (23.2%) had reduced LVEF (LVEF < 40%) [HFrEF], 265(17.8%) with mid-range LVEF (40% ≥ LVEF < 50%) [HFmEF] and 878 (59.0%) had preserved LVEF (LVEF ≥ 50%) [HFpEF]. Kaplan–Meier curves and log-rank test demonstrated better prognosis for HFpEF compared to HFrEF and HFmEF patients. An adjusted Cox analysis showed a significantly lower risk of mortality for HFpEF (hazard ratio (HR); 0.74; 95% confidence interval (CI) 0.57–0.94) p  = 0.015). Multivariate analyses showed that age, higher New York Heart Association (NYHA) functional class, lower LVEF, chronic kidney disease, atrial fibrillation, anemia, diabetes mellitus and absence of statin and aldosterone antagonist treatment were independent predictors of mortality in HF. Although, prognostic factors varied across the three groups, age was a common predictor of mortality in HFpEF and HFmEF. Conclusions: This study identified the clinical characteristics, long-term mortality and prognostic factors of African HF patients with reduced, mid-range and preserved ejection fractions in a clinical setting.